RAÍZES DA CIÊNCIA POLÍTICA BRASILEIRA:IUPERJ, DCP E A REBELIÃO DAS MINÚCIAS - Mano, Daniel (2013)
Brazilian political thought has passed through intense transformations within a short, but decisive period of time, that gets started with the creation of the Superior Institute of Brazilian Studies (ISEB), in 1956, and reaches its clímax with the creation of the two first post-graduation courses in Political Sciences of Brazil: of UFMG´s Political Sciences Department (DCP) and of Rio de Janeiro´s University Institute of Researchs (Iuperj), in 1967 and 1969, respectively. Thins investigation constitutes, largely, a critical analysis of the objectivity framework and methodological rigor irradiated, in Brazil, from the two courses mentioned above. The argument developed here identifies a dissociation between the philosophies of knowledge and of politics in recent brazilian political thinking, showing its effects of reflexive atrophy and methodological dogmatism